Contemporary issues in public sector accounting and auditing - Grima, Simon; Boztepe, Engin (Contemporary studies in economic and financial analysis ;, 2021)
Despite their broad scope and importance, publications related to public sector accounting and auditing have a limited framework, and do not account for the significant variances in public sector accounting and auditing systems between countries and different subsectors of government. The editors of this book have filled this gap by compiling a collection that combines different aspects of public sector accounting and auditing within a single book. Pooling together existing public sector accounting and auditing practices between countries and preparing a comparative analysis of those practices, the authors analyze the role of the public sector accounting and auditing holistically, and provide a platform to enable ficially sustainable policy making and proper assessment of the relevance of accounting frameworks across the globe. The chapters chronicle the strength and weakness of public sector accounting, auditing and systems, and also critically examine the approaches, recording methods, and international regulations which determine how they operate. Providing a comprehensive account which brings a wide range of countries to the forefront in terms of both comparability and accountability, this study shines a light on the differences in accounting systems between states, and provides timely and accurate information to equip readers to minimize those differences.